PHENOMENOLOGICAL STUDY: CAMPUS SECURITY EXPERIENCE OF THE MINISTRY OF HEALTH'S SURAKARTA HEALTH POLYTECHNIC AS A LAY HELPER IN PROVIDING FIRST AID & CARDIAC ARREST TREATMENT FOR ACCIDENT VICTIMS - Khayudin, Bayu Akbar; Wisnu Kanita, Maria; Kusyani, Asri (Nurse and Health: Jurnal Keperawatan, 2025)
Background: Accidents are events that can occur at anytime and anywhere, including on campus. Campus security plays a strategic role as the vanguard in maintaining security and peace, as well as providing first aid in the event of such incidents. Purpose: Aims of this study is to explore and understand in depth the experience of security officers at the Surakarta Ministry of Health Polytechnic Campus as lay helpers in providing first aid and cardiac arrest treatment for accident victims. Methods: This study used were qualitative with a phenomenological approach. Data analysis used Interpretative Phenomenological Analysis (IPA). The research participants consisted of 5 security officers. Data were collected through in-depth interviews Results: produced five main themes, namely: (1) Immediate first aid measures for victims, (2) Providing first aid according to ability, (3) Limited knowledge and skills in first aid, (4) Helping according to the dictates of conscience as a form of devotion and pride, (5) The need for routine training and coaching. The limitations include Reliance on interview data based on participants' subjective experiences, which has the potential to introduce recall bias and social-desirability bias in describing first aid skills and actions and cardiac arrest management. Conclusion: The experience of security personnel shows the importance of providing first aid skills based on ongoing training so that they are able to act quickly, appropriately, and confidently in emergencies in a health education environment.